2019
DOI: 10.1016/j.jaerosci.2019.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Detailed characterisation of TiO2 nano-aggregate morphology using TEM image analysis

Abstract: A detailed morphological characterisation is performed on flame synthesised TiO 2 nano-aggregates (number of primaries, N < 10) using transmission electron microscopy (TEM) image analysis and mobility measurements. The sizedependent collection efficiency of the TEM sampling method is accounted for with a simple correction for particle deposition through impaction and diffusion. The TEM-derived sizes show excellent agreement with electrical mobility measurements. Primary particle size, aggregate size, and degre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 49 publications
2
15
0
Order By: Relevance
“…A laminar stagnation flame, stabilised by flow stretch, was used to prepare TiO 2 nanoparticles from titanium tetraisopropoxide (TTIP) precursor. Full details of the experimental investigation are presented in (Manuputty et al, 2019b). The premixed gas was heated to 150 • C with exit velocity of 436 cm/s.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A laminar stagnation flame, stabilised by flow stretch, was used to prepare TiO 2 nanoparticles from titanium tetraisopropoxide (TTIP) precursor. Full details of the experimental investigation are presented in (Manuputty et al, 2019b). The premixed gas was heated to 150 • C with exit velocity of 436 cm/s.…”
Section: Methodsmentioning
confidence: 99%
“…Nanoparticle morphology was characterised by analysing TEM images and mobility measurements. Details on the sampling procedure, dilution test and particle characterisation are reported in (Manuputty et al, 2019b), so are not repeated here. Overall, it was found that the particle morphology was sensitive to the TTIP loading but was relatively insensitive to the equivalence ratio.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aggregate projected areas of 2048 randomly selected particles were obtained from image analysis, using the method described in [80], of projections produced using the algorithm given in Appendix B.6. Our base case simulation underpredicts the peak of the aggregate PSD ( Fig.…”
Section: Sensitivitymentioning
confidence: 99%
“…Experimental studies and acquisition of plant data are hindered by elevated temperatures and pressures (>1000 K and several bar), residences times in the order of milliseconds and the chlorine environment. However, useful laboratory studies exist, including the early thin film studies of Ghoshtagore [11] and hot wall reactor of Pratsinis et al [12] as well as many more recent results [13,14,15,16]. In addition to allowing direct study of particulate properties, for example by imaging, such studies provide a means of testing and building numerical models [17,18,19] which allows for rapid investigation of process conditions that are expensive/challenging to realize experimentally.…”
Section: Introductionmentioning
confidence: 99%